Leucoplasia oral e leucoplasia verrucosa proliferativa: um estudo clínico comparativo - Fernandes, Darcy [UNESP] (2015)
The squamous cell carcinoma (SCC) represent more than 95% of all the malignant neoplasia of the oral cavity and most of times these tumors are preceded by clinical conditions that have a potential for malignant transformation called oral potentially malignant disorders (OPMD). Among these, the oral leukoplakia (OL) is the most important OPMD, with an incidence rate of 3.4% and a malignant transformation from 0.2 to 17.5%. A form less recognized and poorly understood of leukoplakia is the proliferative verrucous leukoplakia (PVL) which represents a variant with a persistent and progressive to malignancy behavior, with a malignant transformation ratio up to 70% of cases. Currently, the diagnosis of PVL is only made by the temporal and individual observation of each patient, with the demonstration of clinical and histopathological progression to an SCC. The difficult to stablish an early diagnosis of PVL comes from the overlap of clinical and histopathological features with conventional multifocal OL cases. Therefore, was initially proposed to perform a classification of multifocal OL cases found in the Oral Medicine Service from the Araraquara Dental School - UNESP, between 1995 and 2015, according to the WHO definition (WHO, 2005) and the current suggested diagnostic criteria for PVL by Cerero-Lapiedra (2010) and Carrard (2013). Lately, a comparative analysis was conducted between the clinical and microscopic features from cases of PVL and OL. The results of this study revealed that between 86 cases of OL, 45 presented involvement of two or more setting this as multifocal OL cases. According to the evaluation by two experts, 14/45 were considered true cases of PVL. The classification of the same 45 cases by the WHO definition revealed 21/45 cases as PVL, by the Cerero-Lapiedra 27/45 cases were PVL and 4/45 cases were PVL according to Carrard. Sensitivity, specificity...(Complete abstract eletronic access below)